Desain Silabus Pengembangan Kurikulum PAI Di Era Digital - Mira Silvia; Ameliana Nurahmi; Aliifatus Tsaabitah; Darul Ilmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Implementation Syllabus design is an important component of the curriculum that serves as the main guide in the implementation of learning. The development of digital technology demands innovation in the development of the Islamic Religious Education (PAI) curriculum to remain relevant to the needs of the times. The problems studied include the lack of teacher understanding of digital syllabus design, limited technological infrastructure, and minimal digital pedagogical training as the main inhibiting factors. Therefore, a systematic effort is needed in designing a digital-based PAI curriculum development syllabus that is able to answer these challenges. This study aims to analyze and design a digital-based PAI curriculum syllabus design model that is appropriate to the needs of learning in the modern era. The conclusion of this study is that the implementation of a digital-based PAI syllabus can create a more adaptive, participatory, and contextual learning process with the development of modern educational technology. Keywords: Syllabus Design, Curriculum Development, Digital Learning